Hydraulic effects of biofilms on the design and operation of wastewater forcemains - Michalos, Christopher T., author; Thornton, Christopher I., advisor; Grigg, Neil S., committee member; Julien, Pierre Y., committee member; Williams, John D., committee member (Colorado State University. Libraries, 2016)
The impact of biofouling on wastewater forcemains is generally not accounted for in current design practice and little information is available in literature regarding the effect of wastewater biofilms on forcemain hydraulics. In practice, many engineers select a clean water, new pipe roughness factor, to perform hydraulic calculations which may lead to under-sizing wastewater lift station pumps. Forcemains have to cope with a particularly challenging task; they have to ensure that solids contained in the wastewater (sand, gravel, organics) are readily transported along with the wastewater. Forcemain design standards generally recommend a velocity of 2.0 ft/s (0.6 m/s) to prevent deposition of solids and a velocity of 3.5 ft/s (1.1 m/s) to re-suspend solids that may have settled. To further complicate forcemain design and operation; wastewater lift station pumps generally operate intermittently which requires remobilization of any material that may have settled while the pumps remain idle. Therefore, forcemains must be designed to be self-cleaning in order to prevent solids deposition which could cause increased sulfide production leading to corrosion and odor issues; loss of capacity through a reduction of cross sectional area; or even blockage at low points, or at the toe of an adversely sloped pipe leading to costly removal. The goal of this research is to identify short-comings in current forcemain design practice by 1) evaluating the hydraulic effect of biofilms on the absolute roughness (ks) of forcemains; 2) evaluating the hydraulic effect of biofilms on Hazen-Williams C factor; and 3) determine critical velocity required for sediment transport, air clearing, self-cleansing, and optimal diameter of forcemains, which are not identified in forcemain design standards. Operational data were collected and evaluated for 20 municipal wastewater forcemains located in the United States. Data from previous studies, academic research, reports, and published papers were used to supplement and support research findings. A total of 415 data points obtained from 68 forcemain systems ranging from 3- to 66 inches in diameter were evaluated as part of this research. Results of the hydraulic analysis determined that 44% of the systems evaluated were operating at velocities between 2- and 3.5 ft/s and 16% of systems were operating at velocities less than 2 ft/s; indicating that these systems are over designed and do not provide sufficient velocity to re-suspend solids promoting sedimentation. The hydraulic effect of biofilms on forcemain flow resistance was evaluated and determined that ks and C factor varied with forcemain velocity. Calculated values of ks ranged from approximately 35 mm to 0.01 mm, with larger values occurring at velocities less than 1 m/s (3.3 ft/s). The upper range of ks values are orders of magnitude larger than the standard clean water, new pipe ks value found in literature. C factor results ranged from approximately 30 to 150; approximately 60% of forcemain systems evaluated are operating at C factors less than 100, which is much lower than the recommended values of 130 – 150, depending on pipe material. Results suggest that biofilms effect forcemains in a similar manner regardless of pipe diameter, material, or age. Although velocity was determined to be the principle factor affecting ks and C factor; a comparison of the C factor results to ks results show that C factor is dependent upon both velocity and diameter. Equations were developed to estimate ks and C factor and should be utilized along with the Colebrook-White / Darcy-Weisbach and Hazen-Williams equations to estimate the friction headloss for forcemains. The required design velocity for self-cleansing, sediment transport, air clearing, and economical diameter ranges from approximately 4- to 11 ft/s, depending on diameter. Selecting a design velocity between 2 ft/s (0.6 m/s) and 3.5 ft/s (1.1 m/s) may not be appropriate and the minimum design velocity should be selected upon either the self-cleansing velocity or economical pipe sizing. Although each system should be evaluated to determine the correct minimum design velocity based upon the proposed system properties, these results indicate that the minimum forcemain design velocity should be at least 5 ft/s (1.5 m/s).
Keywords: forcemain hydraulics; forcemain design; forcemains